Role of Mandibular Third Molars in Mandibular Anterior Crowding in a Pakistani Population - Hasnain, Muhammad; Tariq, Shahzonia; Fatima, Monal; Khan, Mohammad Shawaiz; Irfan, Sana; Qaseem, Urwah (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess the impact of mandibular third molars in the development of lower anterior crowding in patients. Study Design: Cross-sectional study. Place and Duration of Study: Department of Orthodontics, Dental College HITEC-Institute of Medical Sciences, Taxila Cantt Pakistan from Aug to Nov 2022. Methodology: Orthopantomograms and casts of 136 patients aged 15 years or above reporting to the Department of Orthodontics were evaluated. Arch length discrepancy was calculated on dental casts and the mandibular third molar position was evaluated on OPGs. The data was collected, and descriptive statistics were drawn from quantitative data using SPSS version 26. Frequency and percentages were recorded for categorical variables. The chi-square test was applied to find out the relation between mandibular third molars and lower anterior crowding. Results: Our study included a total records of 136 patients collected, of which 39(28.7%) were males and 97(71.3%) were females. 111(81.6%) records fell in age group 15-24years, 21(15.4%) in age range 25-34 years and 4(2.9%) in age range of 35-44 years. The relationship between crowding and 3rd molar position revealed a statistically significant association between the two, with a p-value of 0.031. Conclusion: Mandibular third molars do contribute to lower anterior crowding.